2021
DOI: 10.1055/s-0041-1723762
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Mid- to Long-Term Outcomes in Patients Experiencing a Knee Dislocation: A Systematic Review of Clinical Studies

Abstract: Knee dislocations (KDs) are devastating injuries for patients and present complex challenges for orthopaedic surgeons. Although short-term outcomes have been studied, there are few long-term outcomes of these injuries available in the literature. The purpose of this study is to determine factors that influence mid- to long-term clinical outcomes following surgical treatment of KD. A review of the current literature was performed by searching PubMed, the Cochrane Library, and Embase to identify clinical studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
(117 reference statements)
0
3
0
Order By: Relevance
“…Many studies and systematic reviews advocate that acute surgery yields overall better results [22,28,44,50,79] and delayed surgery (after 2-3 weeks) decreases the risk of AF [14,50], whereas others found that acute surgery was not associated with stiffness [21].…”
Section: Timing Of Surgerymentioning
confidence: 99%
“…Many studies and systematic reviews advocate that acute surgery yields overall better results [22,28,44,50,79] and delayed surgery (after 2-3 weeks) decreases the risk of AF [14,50], whereas others found that acute surgery was not associated with stiffness [21].…”
Section: Timing Of Surgerymentioning
confidence: 99%
“…Traumatic knee dislocation (TKD) is mostly caused by high‐energy trauma, leading to serious damage to the tissues around the knee. It used to be a rare injury accounting for 0.02%–0.2% of all orthopaedic injuries 1,2 . However, the incidence might have been underestimated because of misdiagnoses and spontaneous knee reduction 3 .…”
Section: Introductionmentioning
confidence: 99%
“…It used to be a rare injury accounting for 0.02%–0.2% of all orthopaedic injuries. 1 , 2 However, the incidence might have been underestimated because of misdiagnoses and spontaneous knee reduction. 3 Additionally, morbidity may rise with the increase in high‐energy trauma, low‐velocity injuries (contact sports), or ultralow‐velocity injuries among obese populations.…”
Section: Introductionmentioning
confidence: 99%